Male Role Norms, Knowledge, Attitudes, and Perceptions of Colorectal Cancer Screening among Young Adult African American Men - Rogers, Charles R.; Goodson, Patricia (Frontiers in Public Health, 2014)
Racial disparities in health among African American men in the United States are extensive. In contrast to their White counterparts, African American men have more illnesses and die younger. African American men have colorectal cancer (CRC) incidence and mortality rates 25% and 50% higher, respectively, than White men. Due to CRC’s younger age at presentation and high incidence among African American men, CRC screening is warranted at the age of 45 rather than 50, but little is known about younger African American men’s views of CRC screening. Employing survey design, the purpose of the study was to describe the male role norms, knowledge, attitudes, perceived subjective norms, and perceived barriers associated with screening for CRC among a non-random sample of 157 young adult African American men (ages 19-45). Sixty-seven percent of the study sample received a passing knowledge score (85% or better), yet no significant differences were found among the three educational levels (i.e., low, medium, high). More negative attitudes towards CRC screening correlated with the participants’ strong perceptions of barriers, but no extremely negative or positive male role norms and perceived subjective norms were found. The factors significantly associated with attitudes were family history of cancer (unsure), work status, and perceived barriers. Findings from this study provide a solid basis for developing structured health education interventions that address the salient factors shaping young adult African American men's view of CRC and early detection screening behaviors.